Burnout Syndrome and the Performance of Full-Time Faculty at a Private University in South Lima, 2023 - LEON VERGARA, RAFAEL RENE; Cano Gamarra, Harold Walter; Campos Rosendo, Nelson Jesús; Montenegro Carrillo, Pedro Martin; Navas Gotopo, Soratna Verónica; Flores Perozo, Inés del Carmen; Pecho Rivera, María Cristina (LACCEI, 2024)
The objective of the study was to determine the relationship between the prevalence of Burnout syndrome and its impact on the performance of full-time teachers at a private university in South Lima. Methodologically, it was oriented towards the quantitative approach, under the positivist paradigm with a non-experimental correlational design. The study sample was made up of 63 teachers who work full time. The technique that was used to collect the information was the survey. The standardized MBI (Maslach Burnout Inventor) questionnaire (online form) was used as an instrument. The technique implemented to validate it was Expert Judgment. To determine its reliability, a pilot test was applied and processed in the SPSS computer program. The degree of confidence was measured with Cronbach’s Alpha coefficient. The results obtained reveal that the majority of participants claim to have levels of emotional exhaustion, high levels of personal accomplishment and have high levels of depersonalization. Regarding this, it is verified that there is no significant incidence between Burnout and the performance of teachers who work full time, since the majority is in the Excellent indicator.